2020
DOI: 10.22541/au.159560819.90629469
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Folic Acid Supplementation in Postmenopausal Women with Hot Flushes: Phase III Randomised Double-Blind Placebo-Controlled Trial

Abstract: Where a licence is displayed above, please note the terms and conditions of the licence govern your use of this document.When citing, please reference the published version. Take down policyWhile the University of Birmingham exercises care and attention in making items available there are rare occasions when an item has been uploaded in error or has been deemed to be commercially or otherwise sensitive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 21 publications
2
3
0
Order By: Relevance
“…We found in our study there is statistical signi cance difference between the two groups in the fourth week regarding mean hot ash score where (p < 0.002). Matching to our study, the randomized control trial in England by Ewies et al 2020 showed that folic acid gave greater bene t in reducing the hot ash score in postmenopausal women when compared with placebo. However; the difference between two groups did not reach statistical signi cance which is inconsistent with this study result which revealed statistically signi cant difference in the fourth week severity after treatment [17].…”
Section: Discussionsupporting
confidence: 54%
See 4 more Smart Citations
“…We found in our study there is statistical signi cance difference between the two groups in the fourth week regarding mean hot ash score where (p < 0.002). Matching to our study, the randomized control trial in England by Ewies et al 2020 showed that folic acid gave greater bene t in reducing the hot ash score in postmenopausal women when compared with placebo. However; the difference between two groups did not reach statistical signi cance which is inconsistent with this study result which revealed statistically signi cant difference in the fourth week severity after treatment [17].…”
Section: Discussionsupporting
confidence: 54%
“…Matching to our study, the randomized control trial in England by Ewies et al 2020 showed that folic acid gave greater bene t in reducing the hot ash score in postmenopausal women when compared with placebo. However; the difference between two groups did not reach statistical signi cance which is inconsistent with this study result which revealed statistically signi cant difference in the fourth week severity after treatment [17]. Also, this study is not consistent with the study of El-Ghobashy et al, 2021 which was not able to demonstrate that folic acid had a greater bene t in reducing hot ash score over 12 weeks in postmenopausal women when compared with placebo [13].…”
Section: Discussionsupporting
confidence: 54%
See 3 more Smart Citations